Circling in on Convective Self‐Aggregation. Issue 20 (11th October 2021) - Nissen, Silas Boye; Haerter, Jan O.
Abstract: In radiative‐convective equilibrium simulations, convective self‐aggregation (CSA) is the spontaneous organization into segregated cloudy and cloud‐free regions. Evidence exists for how CSA is stabilized, but how it arises favorably on large domains is not settled. Using large‐eddy simulations, we link the spatial organization emerging from the interaction of cold pools (CPs) to CSA. We systematically weaken simulated rain evaporation to reduce maximal CP radii, R max, and find reducing R max causes CSA to occur earlier. We further identify a typical rain cell generation time and a minimum radius, R min, around a given rain cell, within which the formation of subsequent rain cells is suppressed. Incorporating R min and R max, we propose a toy model that captures how CSA arises earlier on large domains: when two CPs of radii r i, r j ∈ [ R min, R max ] collide, they form a new convective event. These findings imply that interactions between CPs may explain the initial stages of CSA. Plain Language Summary: Convective self‐aggregation (CSA) describes the emergence of persistently dry, cloud‐free areas in numerical simulations. It has been suggested as a possible mechanism for tropical cyclone formation and large‐scale events such as the Madden‐Julian Oscillation. Some understanding of the persistence of CSA exists. However, how CSA initially emerges remains poorly understood. Recently, the dynamics of cold pools (CPs) have been associated with the organization of convective events. CPs are radially expanding pockets of dense air that form under precipitating thunderstorms. In this work, we ask how weakening CPs could facilitate the emergence of CSA. By analyzing high‐resolution numerical simulations, we show that reducing rain evaporation shortens the time before CSA starts. These simulations demonstrate that CPs reach greater radii when rain evaporation is large. Besides, we find that new convective events occur near the point where two CPs collide. Finally, we report a minimum CP radius within which CPs are too negatively buoyant to initialize new convective events. Building on these numerical findings, we propose a simple idealized mathematical model that approximates CPs as expanding and colliding circles. We show that this model can capture the emergence of CSA. We conclude that the lack of CPs facilitates CSA. Key Points: Smaller cold pool radii in large‐eddy simulations diminish the time to reach convective self‐aggregation We report cold pools' generation time and suppression radius by evaluating the distance between rain events connected in time A mathematical model captures the effect of domain size, suppression radius, and maximum cold pool radius in convective self‐aggregation